2022
DOI: 10.3390/w14050749
|View full text |Cite
|
Sign up to set email alerts
|

The Circular Economy Approach to Improving CNP Ratio in Inland Fishery Wastewater for Increasing Algal Biomass Production

Abstract: In this work, the capacity of wastewater from an inland fishery system in Colombia (Norte de Santander) was tested as culture medium for Chlorella sp. and Scenedesmus sp. Due to insufficient N and P concentrations for successful algae growth, the effect of wastewater replenishment with NO3, PO4, and Na2CO3 or NaHCO3 as a carbon source was analyzed using a three-factor nonfactorial response surface design. The results showed that the addition of NaNO3 (0.125 g/L), K2HPO4 (0.075 g/L), KH2PO4 (0.75 g/L), and NaHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…One of the main problems in the sustainable usage of inland fisheries wastewater is its low nitrogen concentration (especially nitrate) and phosphate (orthophosphate) bioavailable to produce large concentrations of algal biomass [31,32]. Therefore, there is a chance that the extra addition of NO 3 − and PO 4 − into the production system may be found in the exhausted media, which, in turn, can contribute directly to freshwater eutrophication and marine eutrophication indicators, generating a high pollution load to the system under assessment (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main problems in the sustainable usage of inland fisheries wastewater is its low nitrogen concentration (especially nitrate) and phosphate (orthophosphate) bioavailable to produce large concentrations of algal biomass [31,32]. Therefore, there is a chance that the extra addition of NO 3 − and PO 4 − into the production system may be found in the exhausted media, which, in turn, can contribute directly to freshwater eutrophication and marine eutrophication indicators, generating a high pollution load to the system under assessment (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The alga used in this study is a strain of Chlorella sp. (CHLO_UFPS010), previously isolated in another study [32]. The biomass production kinetics, NO 3 − and PO 4 − consump-tion kinetics were obtained from García-Martínez et al [32] and the data on CO 2 removal, energy consumption, mass transfer, and wastewater were obtained from García-Martínez et al [31].…”
Section: Production Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of biological processes include environmental compatibility, competitive cost, non-hazardous metabolites, and reduced water consumption [19]. In recent times, microalgae and cyanobacteria have emerged as sustainable remedies for eliminating harmful substances present in various wastewater types, such as agricultural runoff [20], domestic wastewater [21], agroindustrial wastewaters [22][23][24][25], and landfill leachate [26]. It was reported that Cosmarium species could attenuate malachite green dye at temperatures of 5-45 • C and pH 9, demonstrating its ability to treat wastewater containing this pollutant [27].…”
Section: Introductionmentioning
confidence: 99%